(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تم في هذا البحث تقديم عرض شامل لخوارزمية تنظيم تيخانوف، ومن ثم دراسة تحليلية لآلية عملها. استخدمت هذه الخوارزمية في حساب طيف توزع كثافة الحالات المتوضعة في الفجوة الحركية لأنصاف النواقل غير المتبلورة من النوع a-Si:H (السيلكون الأمورف المهدرج) بطريقة التيار الضوئي الثابت. بعد ذلك تم عرض نتائج حساب أطياف توزع كثافة الحالات في الفجوة الحركية لـ a-Si:H تأسيساً على خوارزمية تنظيم تيخانوف، وتفسير هوية القمم الموجودة في هذه الأطياف وربطها بالتركيب الذري للسيلكون الأمورف المهدرج. وأخيراً أجريت مقارنة بين النتائج التي تم الحصول عليها في هذا البحث وتلك التي تم الحصول عليها من خلال دراسات سابقة من أجل عينات مشوبة بذرات الفوسفور والبور مما يؤكد صحة دراسة خوارزمية التنظيم المطروحة في هذا البحث. This research presents a panorama of the Techanoff regularization algorithm and an analytic study of its mechanism. This algorithm is used in the calculation of distribution spectra of density of states localized in mobility gap of non-crystal semiconductors type a-Si:H (amorphous hydrogenated silicon) by constant photocurrent method. Results of calculation distribution spectra of density states of this algorithm are presented. The interpretation of essence of peaks existing in spectra and connecting it with atomic structure of amorphous hydrogenated silicon was done. Finally, a comparison is done between the results obtained in this research and that obtained through previous studies for samples doped with phosphor and bore atoms. This confirms the verifying of the study of the regularization algorithm presented in this research.